Synthesis and properties of high MW Poly(D,L-lactic acid)s by direct thermal condensation - Shin, GI; Kim, JH; Kim, SH; Kim, YH (POLYMER SOC KOREA, 1997)
Poly (L-lactic acid), (PLLA) and its D,L-copolymers have been prepared by direct polycondensation method and their thermal and mechanical properties were examined. A multifunctional alcohol, dipentaerythritol, was introduced as a branching monomer in the preparation of PLLA and D,L-copolymers with star-shaped macromolecular structure to overcome the molecular weight limitation problems in the direct condensation of lactic acid. High molecular weight polymers with inherent viscosity values within the range of 0.7 similar to 1.0 dL/g (M-n of about 30,000-40,000 daltons by GPC) were prepared and cast into the transparent, flexible films. Thermal analysis showed that the glass transition temperatures of the polymers were within the range of 45 similar to 55 degrees C. The melting temperature and degree of crystallinity decreased as the number of D-lactic acid unit in the copolymer increased. These star-shaped PLLA and D,L-copolymers had a slightly lower decomposition temperature than that of the linear poly (lactic acid), implying that the branched one has less thermal stability. It was found, however, that they showed good mechanical properties, and that the brittle nature of PLLA could be quite improved in D,L-copolymers as proved by the tensile strength measurements.